(untitled) (Medico Legal Update, 2021)
Background: Due to the vast spread of corona virus, lockdown was announced in many countries, and hence many people are facing psychological, physical, economic and social changes. Students at the college experience a variety of sleep problems which can have a direct effect on academic success, health and mood. Sleep disruption and excessive daytime sleep are common problems for students. Subject and Method: 141 college students between the age of 17 to 24 were taken from various colleges. The structured Pittsburgh Sleep Quality Index was used and was circulated amongst students through Google forms and the sleep log, and demographic sheet was used to test sleep length, daytime sleepiness and related sleep issues. Study Design: A cross sectional study. Results: The result, on the basis of the sleep pattern of college students, was classified into 5 categories: (healthy sleep pattern, mild, moderate, severe and worst). 53.90% out of 141 respondents o had healthy sleep pattern range (0-5), 39.71% had mild sleep pattern range (6-10), 4.96% out of 141 respondents had moderate sleep pattern range (11-15), and 1.41% out of 141 respondents had severe sleep pattern range (16-20). Conclusion: In our study we found that during the lockdown majority of college students had a healthy sleep pattern and least of the college students had a severe sleep pattern range.